2003
DOI: 10.1007/s00253-002-1152-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bacterial poly(3-hydroxybutyrate) synthesis genes in hairy roots of sugar beet (Beta vulgaris L.)

Abstract: Three genes from Ralstonia eutropha necessary for poly(3-hydroxybutyrate) (PHB) synthesis were introduced into the hairy roots of sugar beet. Transformation of a vector construct harbouring the PHB genes, each fused to the coding region of the pea ribulose-bisphosphate carboxylase plastid targeting sequence, resulted in 20 transgenic hairy-root clones, producing up to 55 mg high molecular PHB/g dry weight, as identified by gas chromatography, gel permeation chromatography and HPLC. Accumulation of PHB polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…PHB synthesis using genetic engineering approaches was reported in some plants, including switchgrass (Somleva et al 2008), sugarcane (Purnell et al 2007), sugar beet (Menzel et al 2003), tobacco (Lossl et al 2005), flax (Wrobel et al 2004), Arabidopsis thaliana (Kourtz et al 2005), rape, and corn (Poirier 2002).…”
Section: Eukaryotic Phamentioning
confidence: 99%
“…PHB synthesis using genetic engineering approaches was reported in some plants, including switchgrass (Somleva et al 2008), sugarcane (Purnell et al 2007), sugar beet (Menzel et al 2003), tobacco (Lossl et al 2005), flax (Wrobel et al 2004), Arabidopsis thaliana (Kourtz et al 2005), rape, and corn (Poirier 2002).…”
Section: Eukaryotic Phamentioning
confidence: 99%
“…If all of this is converted to PHA, with a yield factor of 33% (Anderson and Dawes, 1990), 4 tonnes of PHA could be obtained per hectare. In contrast, as sugar beet produces 17 tonnes of dry root biomass per hectare, a transgenic sugar beet would need to contain at least 23% PHA in total root biomass, which is perhaps a feasible target considering that 5.5% PHB has been synthesized in sugar beet hairy root cultures (Menzel et al, 2003). Alternatively, the economics of PHA production could be improved by synthesizing PHA in a part of the plant Renewable polymers from plants 693 that is currently not harvested or used, such as the stover of corn or the leaves of sugar beet or sugar cane.…”
Section: Polyhydroxyalkanoatesmentioning
confidence: 99%
“…The values obtained in this study were in line with other studies that looked at different plants, though the transformed genes and targeting techniques we used were not the same: 20-100 mg gFW Ϫ1 in Arabidopsis (Poirier et al 1992), 14% DW in Arabidopsis (Nawrath et al 1994), less than 10 mg gFW Ϫ1 in tobacco (Nakashita et al 1999), 0-7.7% FW in Brassica (Houmiel et al 1999), 4% FW in Arabidopsis (Bohmert et al 2000), 2 to 8 ppm DW in tobacco (Nakashita et al 2001), maximal values of 3.2 mg gDW Ϫ1 in tobacco, 0.09 mg gDW Ϫ1 in potato, and 132 mg gDW Ϫ1 in Arabidopis (Bohmart et al 2002), 1.7% DW in tobacco (Lössl et al 2003), 55 mg gDW Ϫ1 in sugar beet (Menzel et al 2003), and 4.62 mg gFW Ϫ1 in flax (Wróbel et al 2004). It has been reported that growth retardation often accompanies the transformation, as is the case in tobacco (Lössl et al 2003).…”
mentioning
confidence: 99%